Tracing the Development of Arbitration Regime in Nepal to Present Modern Arbitration Practice: A Glimpse (Tribhuvan University Law Journal, 2025)
Arbitration in Nepal can be traced back to informal practices that existed long before the formal recognition of arbitration through statutory measures. The roots of arbitration in Nepal are embedded in scattered provisions related to arbitration found in various statutes. To fully grasp the current arbitration landscape in Nepal, it is essential to appreciate the gradual evolution of arbitration within the country’s legal system. This study aims to provide a comprehensive exploration of the historical development of commercial arbitration in Nepal. It employs a qualitative doctrinal analysis approach, primarily focusing on the legislative frameworks that have contributed to the evolution of arbitration in Nepal. It’s important to note that this study does not delve into judicial rulings, or the legal precedents established by the Supreme Court of Nepal.The recognition of arbitration in Nepal has evolved over time, with legal provisions gradually taking shape to accommodate the needs of businesses and individuals seeking alternative dispute resolution mechanisms. The journey to the formal legislative framework has been marked by changes and adaptations in response to the changing demands of Nepal’s growing economy and international trade relationships. By focusing on the legislative aspects, this study sheds light on how arbitration has been integrated into the Nepali legal system, making it an indispensable tool for resolving commercial disputes. It offers insights into the key laws, regulations, and amendments that have shaped the arbitration landscape in Nepal, providing a solid foundation for understanding the current state of arbitration in the country.